Korelasi Antara Panjang Tulang Humerus Dengan Tinggi Badan Suku Batak di Universitas HKBP Nommensen Medan - Roy Abednego Purba; Saharnauli Janna Verawaty Simorangkir; Rebecca Rumesty Lamtiar (Nommensen Journal of Medicine, 2020)
Background: Height is one of the data in the forensic identification process. The process of measuring height will be difficult if the bones or body parts found are not intact. Estimation of height can be facilitated by measuring the dimensions of long bones, one of which is the humerus. Analysis of the correlation of humerus bone length with height can support in determining the formula for estimating height based on humerus bone length. This study aims to determine the correlation between humerus bone length and Batak tribe height at HKBP Nommensen University, Medan. Method: This research was a descriptive analytic study with cross sectional design. The research sample was 72 students, lecturers, and employees consisting of 27 men and 45 Batak tribe women who met the inclusion and exclusion criteria at HKBP Nommensen University, Medan. Sampling is done by purposive sampling. Data analysis in this study was carried out by means of univariate and bivariate analysis using the Pearson and Spearman test methods to determine the correlation between humerus bone length variables and height variables. Result: The results obtained there is a strong correlation between humerus bone length and height in the Batak tribe with a correlation coefficient value r = 0.784 (p <0.05). Based on gender, men have weak and insignificant correlation strength with correlation coefficient r = 0.449 (p> 0.05) while women have strong and significant correlation r = 0.771 (p <0.05). Conclusion: There is a strong correlation between humerus bone length and Batak tribal height at HKBP Nommensen University, Medan.